2020
DOI: 10.5155/eurjchem.11.4.291-297.2002
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric method for determination of ranitidine hydrochloride in bulk and in pharmaceutical preparation using ninhydrin

Abstract: A simple, sensitive and reproducible method for the determination of ranitidine hydrochloride in pharmaceutical preparations was investigated. This spectrophotometric method was based on the formation of a deep red color product with ninhydrin in basic media and the absorbance measured at λmax = 480 nm. The reaction occurs at 45 °C with pH = 10 having a contact time of 38 minutes. Under the optimum conditions, Beer’s Law is obeyed in the concentration range of 8.98×103 - 9.90×104 µg/L. The coefficient of correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…An analytical comparison was performed in Table 6 to show the advanced sensitivity and efficiency of the suggested potentiometric modified sensors for the determination of RNT with other previously reported analytical techniques [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. The comparative results showed that the suggested modified sensors using metal oxide nanoparticles exhibited higher sensitivity over a wide concentration range than those reported by the previously developed sensors.…”
Section: Resultsmentioning
confidence: 99%
“…An analytical comparison was performed in Table 6 to show the advanced sensitivity and efficiency of the suggested potentiometric modified sensors for the determination of RNT with other previously reported analytical techniques [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. The comparative results showed that the suggested modified sensors using metal oxide nanoparticles exhibited higher sensitivity over a wide concentration range than those reported by the previously developed sensors.…”
Section: Resultsmentioning
confidence: 99%
“…In this research, a new spectrophotometric method for the determination of Cr (III) using ninhydrin was investigated, Ninhydrin in this research acts as chromogenic agent [12]. The ability of ninhydrin (a bidentate ligand) to function as an analytical reagent was the subject of some interesting and practical data presented in this work [13] [14] [15]. The chromogenic reagent in this procedure was ninhydrin.…”
Section: Introductionmentioning
confidence: 99%